UNDERSTANDING CRITERIA OF EFFECTIVE TEACHER PROFESSIONAL DEVELOPMENT: PERSPECTIVES OF ISLAMIC HIGH SCHOOL TEACHERS IN ACEH - Fadliadi Ubit (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
This cross-sectional qualitative study was conducted to understand teachers’ expectations of their professional development that will inform the policy and practice of effective teacher professional development programs. The participants of the study were in-service English teachers who were alumni of professional development programs held at a training centre in Banda Aceh-Indonesia under the Ministry of Religious Affairs (MoRA). Data were collected using semi-structured interviews and data collected were analysed using thematic analysis. The findings show that teachers had high expectations when attending a professional development program. Another significant findings were teachers expected qualified trainers both instructional and interactional; the provision of good quality training facilities, resources, and infrastructure; adequate and equal teachers’ access to professional development that meets their professional development’s needs, career and learning journey. These elements were perceived by teacher participants as important criteria for effective teacher professional development, especially in Aceh’s context.  Keywords: teachers’ expectation; teacher professional development; trainer’s quality; learning environment